An examination of reciprocal associations between substance use and effortful control across adolescence using a bifactor model of externalizing symptoms. (October 2021) - Paige, Katie J.; Meisel, Samuel N.; Colder, Craig R.
Abstract: Early adolescence is thought to represent a window of vulnerability when exposure to substances is particularly harmful, partly because the neurotoxic effects of adolescent substance use may derail self-regulation development. However, previous studies fail to account for externalizing symptoms, such as aggression and delinquency, that accompany adolescent substance use and may also derail the development of self-regulation. The current study aims to clarify whether the neurotoxic effects of adolescent substance use are associated with deficits in effortful control (EC) after accounting for externalizing symptoms and to examine reciprocal relationships between EC, externalizing symptoms, and substance use. A longitudinal sample of adolescents ( N = 387) was used to estimate bifactor models of externalizing symptoms across five assessments ( M age = 11.6 to 19.9). The broad general externalizing factors were prospectively associated with declines in EC across adolescence and emerging adulthood. However, the narrow substance use specific factors were not prospectively associated with EC. Findings suggest that the broader externalizing context, but not the specific neurotoxic effects of substance use, may hamper self-regulation development. It is critical to account for the hierarchical structure of psychopathology, namely externalizing symptoms, when considering development of EC.